2013
DOI: 10.1111/ssqu.12065
|View full text |Cite
|
Sign up to set email alerts
|

Does Walkability Influence Housing Prices?

Abstract: Objective. We examine the effects of neighborhood walkability on house values. Recent research claims that walkability makes homes more valuable, ceteris paribus. We contend that some studies report a spurious effect of walkability because of differences between areas with high and low walkability. Methods. We replicate the positive effect of walkability on prices for single-family homes and condominiums in Miami, Florida, using a unique data set of house values and characteristics. We employ a fixed effects r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Some studies (Pivo and Fisher 2009;Boyle, Barrilleaux, and Scheller 2013) use walk score (Walk Score 2014) to quantify walk accessibility and its impact on residential, retail, and industrial property values. Walk score is calculated by measuring the straight-line distance between a property and its nearest educational, retail, food, recreational, and entertainment destinations.…”
Section: Methods To Quantify Walk Accessibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies (Pivo and Fisher 2009;Boyle, Barrilleaux, and Scheller 2013) use walk score (Walk Score 2014) to quantify walk accessibility and its impact on residential, retail, and industrial property values. Walk score is calculated by measuring the straight-line distance between a property and its nearest educational, retail, food, recreational, and entertainment destinations.…”
Section: Methods To Quantify Walk Accessibilitymentioning
confidence: 99%
“…Apart from the potential environmental and social benefits, recent empirical studies also illustrate that a more walkable environment can improve residential and commercial property values (Pivo and Fisher 2009;Boyle, Barrilleaux, and Scheller 2013). In addition, the emerging domain of responsible property investing (Pivo and Fisher 2009) seeks to promote real estate investments that benefit both investors and the common good.…”
Section: Introductionmentioning
confidence: 99%
“…For example, dwelling related aspects are the type and size of the dwelling, the number of rooms or the amount of land that goes with it. Among others, neighbourhood related aspects are the walkability of the surrounding, the level of crime, the quality of proximate schools, the racial or ethnic population composition, green spaces or parks, the effects of investments in amenities, or the presence or absence and the quality of sidewalks in walkable and in car-dependent residential areas (Anderson & West, 2006;Boyle, Barrilleaux, & Scheller, 2014;Cervero & Duncan, 2004;Li et al, 2015;Lynch & Rasmussen, 2001;Song & Knaap, 2004). Accessibility variables such as distances to the central business district (CBD), motorways and public transport are also described to correlate with housing prices (Hess & Almeida, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from positive correlations, insignificant or negative correlations were also observed. Boyle, Barrilleaux [46] found that walkability's impact on housing value is statistically insignificant in Miami, Florida. Similarly, in Cortright [34], two out of the 15 studies housing markets did not show positive correlation between walkability and housing value, and one of them (Las Vegas) exhibited negative correlation, while another one (Bakersfield) showed insignificant correlation.…”
Section: Introductionmentioning
confidence: 98%
“…The economic value of a walkable neighborhood was obtained by encouraging economic transactions and social exchanges [1,11,42]. A growing number of studies have contributed to the debate on the relationship between walkability level and property value [1,10,[34][35][36][42][43][44][45][46]. For instance, it was reported that walkability level is positively correlated with residential estate value in 13 out of 15 housing markets sampled in U.S. metropolitan areas [34].…”
Section: Introductionmentioning
confidence: 99%